Volvulus of the stomach and wandering spleen after repair of congenital diaphragmatic hernia: unexpected manifestations in a neonate - Noboru Oyachi; Fuminori Numano; Tamami Fukatsu; Atsushi Nemoto; Atsushi Naito (Surgical Case Reports)
Abstract Background Congenital diaphragmatic hernia (CDH) is sometimes associated with complications involving herniation of intrathoracic organs, which further increase mortality rate. We encountered a case of postoperative gastric and splenic volvulus shortly after left CDH repair in a female neonate who was treated with gastropexy. Case presentation At 39 weeks gestation, a female patient with left Bochdalek CDH was delivered (birth weight: 3748 g, Apgar score: 3/4). The patient was provided ventilator support with nitric oxide. After pulmonary hypertension improved, CDH repair was performed via the abdominal approach on day 7. The stomach, small intestine, large intestine, and spleen were herniated through a diaphragmatic defect of 4 × 2 cm. Although the diaphragm was directly closed, it was tight and the reconstructed diaphragm “dome” was shallow, restricting space for the spleen and stomach. Nonetheless, the spleen was positioned in the left upper abdomen and the stomach was positioned medially. The postoperative course was complicated by organo-axial gastric volvulus, and laparotomy was performed on day 14. In addition to the gastric volvulus, we confirmed a wandering splenic volvulus. The spleen was easily detorted and returned to the left upper abdomen. However, the patient experienced relapse of gastric volvulus without splenic volvulus. Gastropexy was performed electively on day 47. Postoperatively, the patient could be fed orally, and the patient’s development was satisfactory 6 years after surgery. Conclusions The cause of these rare complications appeared to be tight direct diaphragmatic closure, which reduced space for the spleen and stomach beneath the left diaphragm.